Optimal taxation with capital accumulation and wage bargaining - Tapio Palokangas (Institute for the Study of Labor (IZA), 2003)
This study examines optimal taxation in a unionized economy in which households save capital. The main findings are as follows. Judd?s (1985) and Chamley?s (1986) classical results of zero taxation on capital income holds. This is true independently of workers? savings behaviour or the capitalists? weight in the social welfare function. The steady-state optimal tax rates on wages and employment are specified. The consumption tax is needed for revenue raising purposes.
Keywords: J51; H21; 330; wage settlement; optimal taxation; capital accumulation; Optimale Besteuerung; Investition; Sparen; Lohnbildung; Gewerkschaftlicher Organisationsgrad; Theorie